An Application of a Multicriteria Model to Assess the Quality of Local Governance. Issue 4 (July 2019) - F. da Cruz, Nuno; Marques, Rui Cunha
This article presents a method to assess the quality of local governance practices. The multicriteria decision analysis modeling approach is illustrated through a real application (Portuguese municipalities). To define the criteria, performance descriptors, and reference levels in each dimension of local governance, and to account for the differences in preference of scoring in each criterion, the judgments of legitimate stakeholders were considered through decision conferencing. The constructed "Municipal Governance Indicator" is calculated for the case of Lisbon to show the outputs of the model and its potential usefulness.